The Relationship Between the Status of Unnecessary Accommodations Being Made to Unconfirmed Food Allergy Students and the Presence or Absence of a Doctor's Diagnosis - Yurika Ganaha; Minoru Kobayashi; Yonathan Asikin; Taichi Gushiken; Sumie Shinjo (MDPI AG, 2015)
The present study investigated the current state of unnecessary children food allergy accommodation and the medical efforts to confirm the existence of food allergies in school lunch service kitchens in Okinawa, Japan, including kitchens accommodating food allergy students by requiring medical documentation at the start and during provisions being made (Double Diagnosis), requiring medical documentation at the start only (Single Diagnosis), and with no medical documentation (Non-Diagnosis). Unnecessary accommodations are being made to unconfirmed food allergy students, wherein the more medical consultation was required, the lower the food allergy incident rate was and the more food allergens were diagnosed (Non-Diagnosis > Single Diagnosis > Double Diagnosis). This study suggests the possibility that unconfirmed food allergy students may be receiving unnecessary food allergy accommodations per school lunches, and the number of unnecessary food allergy provisions being made could be reduced by requiring medical documentation at the start and during these provisions.